Preparatory longswing techniques for dismounts on uneven bars - Tighe, D.; Irwin, G.; Kerwin, D.; Gittoes, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to quantify the biomechanical differences between two methods of performing the preparatory longswing preceding the double layout dismount. Video images of 6 female Olympic level gymnasts performing the double layout dismount (3 = straddle preparatory longswing, 3 = dished preparatory longswing) were recorded using two synchronised 50 Hz digital cameras. 3D DLT reconstructed coordinates were combined with inertia values to define discrete release variables including vertical and horizontal velocity of the mass centre, release angle and angular momentum about the gymnast`s mass centre. Joint angular kinematics at the hips and shoulders were contrasted with particular reference to the hip functional phase. Based on the reported release parameters the straddle longswing could be considered preferential.